2016
DOI: 10.1088/1361-6382/34/2/024001
|View full text |Cite
|
Sign up to set email alerts
|

Candidates for a possible third-generation gravitational wave detector: comparison of ring-Sagnac and sloshing-Sagnac speedmeter interferometers

Abstract: Speedmeters are known to be quantum non-demolition devices and, by potentially providing sensitivity beyond the standard quantum limit, become interesting for third generation gravitational wave detectors. Here we introduce a new configuration, the sloshing-Sagnac interferometer, and compare it to the more established ring-Sagnac interferometer. The sloshing-Sagnac interferometer is designed to provide improved quantum noise limited sensitivity and lower coating thermal noise than standard position meter inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The achieved sensitivity by the first generation of interferometric detectors (LIGO (Abbott et al 2009), Virgo (Acernese et al 2008), GEO 600 (Grote 2008), and TAMA (Takahashi 2004)) was mainly limited by shot noise, mirror thermal noise, and seismic noise, while for the second-generation GW detectors, such as Advanced LIGO (aLIGO) (Harry 2010), Advanced Virgo (AdV) (Acernese et al 2015), KAGRA (Somiya 2012;Aso et al 2013), and LIGO-India (Unnikrishnan 2013) additional fundamental noise sources (such as, photon radiation pressure noise and thermal noise of the test mass suspension) will play a role towards the low-frequency end of the detection band. As expected, the latter noise sources will be more prominent in third-generation GW detectors (Hild et al 2011;Punturo & Luck 2011;Huttner et al 2017), particularly due to the fact that the main aim of these detectors is to probe the low-frequency band; as low as a few Hz (Hild et al 2010). This low-frequency range is one of the main driving forces of third-generation GW detectors, since it encapsulates some rich information on the cosmological evolution of the Universe (see for instance, Punturo et al 2010a;Sathyaprakash et al 2010Sathyaprakash et al , 2012Srivastava et al 2019;Bachega et al 2020;Chen et al 2020;Maggiore et al 2020;Sharma & Harms 2020;Yang et al 2019bYang et al , 2020aZhang et al 2020, and references therein).…”
Section: T H I R D -G E N E R At I O N G W D E T E C To R Ssupporting
confidence: 64%
“…The achieved sensitivity by the first generation of interferometric detectors (LIGO (Abbott et al 2009), Virgo (Acernese et al 2008), GEO 600 (Grote 2008), and TAMA (Takahashi 2004)) was mainly limited by shot noise, mirror thermal noise, and seismic noise, while for the second-generation GW detectors, such as Advanced LIGO (aLIGO) (Harry 2010), Advanced Virgo (AdV) (Acernese et al 2015), KAGRA (Somiya 2012;Aso et al 2013), and LIGO-India (Unnikrishnan 2013) additional fundamental noise sources (such as, photon radiation pressure noise and thermal noise of the test mass suspension) will play a role towards the low-frequency end of the detection band. As expected, the latter noise sources will be more prominent in third-generation GW detectors (Hild et al 2011;Punturo & Luck 2011;Huttner et al 2017), particularly due to the fact that the main aim of these detectors is to probe the low-frequency band; as low as a few Hz (Hild et al 2010). This low-frequency range is one of the main driving forces of third-generation GW detectors, since it encapsulates some rich information on the cosmological evolution of the Universe (see for instance, Punturo et al 2010a;Sathyaprakash et al 2010Sathyaprakash et al , 2012Srivastava et al 2019;Bachega et al 2020;Chen et al 2020;Maggiore et al 2020;Sharma & Harms 2020;Yang et al 2019bYang et al , 2020aZhang et al 2020, and references therein).…”
Section: T H I R D -G E N E R At I O N G W D E T E C To R Ssupporting
confidence: 64%
“…[168] Despite these challenges, much effort was put into pushing the Sagnac scheme into an implementable state for the third generation of gravitational-wave detectors. [138,146,147,[169][170][171] For instance, it was shown that the zero-area Sagnac interferometer is a speedmeter, which can have advantages over position meters, like more conventional Michelson interferometers. [147] Moreover, the sensitivity of the zero-area Sagnac interferometer can be improved upon using ring cavities in the arms and signal recycling, similarly to the illustration in Figure 4 without the elements inside the area delimited by the dashed line, which were a later addition.…”
Section: Third Generation Of Gravitational Wave Detectorsmentioning
confidence: 99%
“…More improvements were suggested with the introduction of a sloshing-Sagnac interferometer, which is made out of two resonant Fabry-Pérot arm cavities in a Michelson configuration linked to a similar, antiresonant cavity running parallel to them. [169] This constitutes the Sagnac configuration represented in Figure 5. When compared to the ring-Sagnac interferometer shown in Figure 4, this device offers an extra degree of freedom for optimizations in the form of the finesse of the sloshing cavity that is separated from the arm cavity.…”
Section: Third Generation Of Gravitational Wave Detectorsmentioning
confidence: 99%
“…Another feature that we notice is the difference between the two readout quadratures in high frequency for three LO options. That can be understood form the equation (27), since for phase quadrature readout, the transfer function of the amplitude quadrature noise is just proportional to sym  , which decrease in high frequency according to equation (17). However, on an alternative homodyne angle as shown in equation (23) and (24), the amplitude noise gets coupled to the readout constantly and dominates in high frequency.…”
Section: Relative Laser Intensity Noise Requirementmentioning
confidence: 99%
“…Back-action noise reduction in speed metres stems from the quantum non-demolition (QND) nature of test mass' velocity [12] as a quantum observable, in contrast to the displacement measured by Michelson interferometers. This advantage of speed metres over position metres at low frequencies inspired the development of several different speed metre topologies [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%